Metastatic mesenchymal chondrosarcoma showing a sustained response to cabozantinib: A case report - Blum, Veronika; Andrei, Vanghelita; Ameline, Baptiste; Hofer, Silvia; Fuchs, Bruno; Strobel, Klaus; Allemann, Anna; Bode, Beata; Baumhoer, Daniel (Frontiers in Oncology, 2022)
Mesenchymal chondrosarcoma is a rare and aggressive sarcoma subtype with high risk for distant metastases and poor prognosis. Currently NCCN- and ESMO-Guidelines recommend using Ewing sarcoma protocols as standard treatment. Nevertheless, in localized disease overall 5-year survival rates are below 50% whereas in metastatic spread median progression-free survival rates of only 5 months can be expected. Here we present a patient with metastatic osseous spread of mesenchymal chondrosarcoma that showed a sustained clinical improvement and a good partial response on imaging over a period of one year when treated with the multi-tyrosine kinase inhibitor cabozantinib. Although we cannot explain the exact mechanism underlying this treatment effect, tumors with similar genetic patterns might respond to the same therapy as well.